PERSEPSI GURU TERHADAP PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN PAI DI SMA MUHAMMADIYAH 18 JAKARTA - Nashrullah; Muhammad Arifin Rahmanto (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze teachers' perceptions of the implementation of the Deep Learning approach in Islamic Religious Education (PAI) learning in grade XII students of SMA Muhammadiyah 18 Jakarta, while simultaneously developing a conceptual model of the Islamic Deep Learning Framework as a novelty in the research. The method used was descriptive qualitative with a field research approach. Data were collected through observation, in-depth interviews, and documentation using a purposive sampling technique. The research subjects consisted of eleven informants: the vice principal for curriculum, two PAI teachers, and eight grade XII students selected based on their active involvement in learning. Data analysis was conducted using thematic analysis and source triangulation techniques to maintain the validity of the findings. The results showed that teachers and students have positive perceptions of the implementation of Deep Learning because it encourages reflective, contextual, and spiritually based learning. The school also supports this implementation through a curriculum policy that integrates the principles of meaningful, mindful, and joyful learning. However, a gap remains between ideals and practices, particularly in mastery of digital literacy and spiritual reflection. The novelty of this research lies in the development of the Islamic Deep Learning Framework, a learning model that integrates the values ​​of monotheism, spiritual reflection, and Islamic digital literacy to create meaningful Islamic Religious Education (PAI) learning that is relevant to the Independent Curriculum.